Misoprostol and mid trimester termination of pregnancy in patients with two previous scars and more at Elwiya Maternity Teaching Hospital - Esraa Reehan; Sahar Jassim Abid; Samar Sarsam; Thikra N Abdulla; Zaid Al-Attar (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to determine efficiency and safety of three misoprostol regimens for 2nd trimester pregnancy termination in individuals with two or more cesarean section scars. Methods: a cross-sectional study included 100 pregnant ladies at 13th-26th weeks gestation with previous two cesarean sections (CSs) who were scheduled for pregnancy termination using misoprostol. Patients were conveniently assigned to 100µg/3h, 200µg/3h or 400 µg/3h regimens. Primary outcome was time to abortion, secondary outcomes were side effect and complications. Results: a significant association was found between number previous CSs and longer time to abortion (p=0.01). A highly significant association was identified between earlier gestational age and longer time to abortion (p<0.001). Lower side effects and complications were associated with 200 µg misoprostol every 3 hours of (p<0.001). Incomplete abortion was the most frequent recorded complication for the successive doses of misoprostol. Conclusions: misoprostol is an effective drug at low doses for pregnancy termination in women with prior two or more caesarean sections. However, its safety needs monitoring of the patient in the hospital to decrease morbidity and mortality behind its use.